2007
DOI: 10.1111/j.1600-065x.2007.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and signaling molecules controlling the transmigration of leukocytes through endothelium

Abstract: Migration of leukocytes into tissue is a key element of innate and adaptive immunity. While the capturing of leukocytes to the blood vessel wall is well understood, little is known about the mechanisms underlying the actual transmigration of leukocytes through the vessel wall (diapedesis). Even a basic question such as whether leukocytes migrate through openings between adjacent endothelial cells (junctional pathway) or through single endothelial cells (transcellular pathway) is still a matter of intensive deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
246
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(249 citation statements)
references
References 161 publications
0
246
1
2
Order By: Relevance
“…Because this suggested that the expression of L1 is regulated by tumor-or infl ammatory cell -derived fac- heterophilic binding partners of L1 involved in DC -EC interactions remain elusive, members of the integrin family are suitable candidates. Indeed, the cross talk between integrins and Ig-like CAMs, such as members of the ICAM and JAM families, is a key step during leukocyte transmigration ( 28 ). In support of this hypothesis, not only has L1 been reported to interact with integrins in other experimental systems ( 10,29,30 ) but L1 homophilic binding upon cell-cell adhesion has been shown to promote integrin recruitment and activation ( 31 ).…”
Section: L1 Homophilic Binding In DC -Endothelium Interactionmentioning
confidence: 53%
“…Because this suggested that the expression of L1 is regulated by tumor-or infl ammatory cell -derived fac- heterophilic binding partners of L1 involved in DC -EC interactions remain elusive, members of the integrin family are suitable candidates. Indeed, the cross talk between integrins and Ig-like CAMs, such as members of the ICAM and JAM families, is a key step during leukocyte transmigration ( 28 ). In support of this hypothesis, not only has L1 been reported to interact with integrins in other experimental systems ( 10,29,30 ) but L1 homophilic binding upon cell-cell adhesion has been shown to promote integrin recruitment and activation ( 31 ).…”
Section: L1 Homophilic Binding In DC -Endothelium Interactionmentioning
confidence: 53%
“…Here, membrane-bound receptors and their cognate ligands may play essential roles (Gomez-Rodriguez et al, 2007;Huang et al, 1999;Hwang and Ki, 2011;Hwang et al, 2000;Peterson, 2003;Vestweber, 2007). The set of receptors and ligands making contact with each other in cells determine the phenotypic changes in those cells during or after the contact.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of endothelial cells increases vascular permeability, initiates inflammatory responses, and recruits leukocytes by the upregulation of the leukocyte adhesion molecules ICAM1, vascular cell adhesion molecule 1 (VCAM1), and E-selectin (41). ICAM1 is minimally expressed on resting endothelial cells and is upregulated in response to inflammatory mediators, such as virus infection and the proinflammatory cytokines IL-1␤, IL-6, and TNF-␣ (31,38).…”
mentioning
confidence: 99%